2014
DOI: 10.1515/jafio-2014-0007
|View full text |Cite
|
Sign up to set email alerts
|

Analysing Farmers’ Use of Price Hedging Instruments: An Experimental Approach

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Considering hedging decisions among German farmers, Anastassiadis et al . () showed that price expectations, attitude regarding risk and storage capacity influenced the risk management strategies of grain farmers.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Considering hedging decisions among German farmers, Anastassiadis et al . () showed that price expectations, attitude regarding risk and storage capacity influenced the risk management strategies of grain farmers.…”
Section: Previous Studiesmentioning
confidence: 99%
“…To limit this bias, Anastassiadis et al. () analyse German cereal producers’ choices to cover risk with forward contracts under controlled test conditions using a discrete choice method.…”
Section: Discussionmentioning
confidence: 99%
“…In this, the study focused on results for Europe. A global perspective does not seem feasible, since European farmers operate under fundamentally different conditions with regard to farm structures, climate, agricultural market structures, and agricultural policy [23]. The European rental market appears promising for the assessed research questions due to the high rental shares, the comparatively high political regulation of agricultural production as well as the fact that in no other region have rental prices risen so sharply in recent years [11].…”
Section: Introductionmentioning
confidence: 99%